Transformation of Indian railways–a story of change, challenges and visionary leadership - Ranjan, Rajesh; Prasad, T; Singh, Rashmi; Tripathi, Saumya (Edelweiss Applied Science and Technology, 2025)
The success or failure of an organization hinges on the leadership qualities of its leaders. Effective leaders assist their subordinates in finding solutions to their challenges. Leadership in Indian Railways involves bringing together resources, formulating strategies, organizing, and controlling activities to achieve set objectives. Additionally, the leaders within Indian Railways are responsible for selecting goals, deciding on actions, and motivating people to carry them out. In essence, leadership in Indian Railways is a management function focused on setting goals and inspiring people to work towards achieving them. Leaders in Indian Railways guide their teams by setting clear objectives and helping subordinates navigate the best path to achieve these goals. Indian Railways leadership can be seen as the art or process of influencing people to work willingly and enthusiastically towards the accomplishment of group goals. The key elements of leadership within Indian Railways include power, a deep understanding of people, the ability to inspire followers, and the leadership style and work environment created within the organization.